Transmittance measurement using scanning LED - Rosmin Elsa Mohan (2019)
In order to measure the transmittance for a large field of view (FOV), a system based on scanning LED is developed. The system mainly consists of tunable LEDs, a glass diffuser and a camera. The LED panel would display different colors in the CIE color space. An algorithm of converting the light wavelength to the RGB values is adopted. The images are captured using a monochrome camera. Depending on the number of colors displayed, the transmittance map for the entire spread of visible colors can be determined. Results are compared with those measured through a spectrometer. The spectral transmittance for the two methods exhibit good similarity. The system provides a means of measuring transmittance with no moving parts and can be extended to other hyperspectral imaging applications.